OC-010 Implementation of a Novel Colonoscopy Performance Index, The Composite Caecal Intubation Rate (CIRC), in a UK Tertiary Centre. (17th August 2016) - Beintaris, I; Spranger, H; Bassett, P; Thomas-Gibson, S
Abstract : Introduction: The Composite Caecal Intubation Rate (CIR c ) has been proposed as a more pragmatic colonoscopy performance index, encompassing three key components; caecal intubation rate (CIR), patient comfort and sedation dose. 1 We calculated CIR c s within a Tertiary Unit (St Mark's Hospital, UK), aiming to assess performance and look for possible correlation between CIR c and adenoma detection rate (ADR). 2 Methods: We analysed all colonoscopies performed by 32 Endoscopists in 12 months. CIR c was the proportion of procedures fulfilling the following criteria; procedure completion, comfort score ≤3 (Gloucester scale) 3 and midazolam dose 0–2 mg. We examined the association between CIR c and annual colonoscopy volume, completion rate, midazolam dose and polyp detection rate (PDR). Finally, we sought for a correlation between CIR c and ADR for 7 Bowel Cancer Screening Programme (BCSP) Endoscopists. Results: Analysis included 5416 colonoscopies. Overall CIR c was 85.6%. There was significant correlation between CIR c and annual colonoscopy volume; all colonoscopists with >250 procedures had CIR c s >85%. The majority of operators with <200 procedures had the lower scores, but still more than 70%. There were Endoscopists with low annual volumes and high CIR c meaning that expert endoscopists with high lifetime (but low annual) volumes can nonetheless deliver high quality colonoscopy. There was also evidence of a negative correlation between midazolam and CIR c, but of no statistical significance. No significant association was observed with CIR or PDR. There was a reasonable positive correlation, albeit non significant, between ADR and CIR c in the BCSP Endoscopists' subgroup. Conclusion: CIR c is a more informative performance index, reflecting key aspects of colonoscopy. Reassuringly, overall CIR c achievement in the Unit was above National Audit data (54.1%). 1 Endoscopists with larger procedure volumes performed better. No significant correlation with ADR was seen, although a positive trend was noted. The small amount of patients included in the ADR analysis group is insufficient to draw definite conclusions. Applying CIR c at a local level may aid in identification of under-performers, although case-mix factors may affect results. References: 1 Valori R, Damery S, Swarbrick E, et al . PWE-057 A composite measure of colonic intubation is better able to distinguish performance of colonoscopy and is associated with higher polyp detection rates. Gut 2014;63 :A148. 2 Corley DA, Jensen CD, Marks AR, et al. Adenoma detection rate and risk of colorectal cancer and death. N Engl J Med 2014;370 :1298–306. 3 Ekkelenkamp VE, Dowler K, Valori RM, Dunckley P. Patient comfort and quality in colonoscopy. World J Gastroenterol 2013;19 :2355–61. Disclosure of Interest: None Declared